Assessing bone banking activities at University of Malaya medical centre - Mohd, S.; Samsuddin, S.M.; Ramalingam, S.; Min, N.W.; Yusof, N.; Zaman, T.K.; Mansor, A. (Springer, 2015)
The main advantage of establishing in-house bone banks is its ability to readily provide allograft bones for local surgeries. Bone procurement activities of our university bone bank during the 10 years of operation were reviewed. Socio-demographic data of donors, types of bone procured, cases of rejected bones and types of allograft bones transplanted are presented. From 179 potential donors, 73 % were accepted with 213 procured bones. Femoral head was the common bone transplanted (45 %), as it was also the most common procured (82 %). Bones were rejected mainly due to non-technical reasons (83 %) rather than positive results of microbiological (13 %) and serological (4 %) tests. Comprehensive data could not be obtained for further analysis due to difficulties in retrieving information. Therefore, quality assurance system was improved to establish more systematic documentations, as the basis of good banking practice with process control hence allowing traceability.